Islamic Educational Management based Culture in Madrasah Diniyah1 Zumrotus Salamah Tawangsari Ã¢â¬â Tulungagung - Subhin, M. Abdillah (EDUKASI: Jurnal Pendidikan Islam, 2017)
The 21st century is the heaviest terrain in the history of development Madrasah Diniyah in some parts of Indonesia, ÃÂ ne ÃÂ of ÃÂ them ÃÂ isÃÂ  Tulungagung ÃÂ and ÃÂ arrounds. ÃÂ In response to the challenges of the times, Madrasah diniyah as an Islamic education organization is expected to strength and develop the Islamic soul as well as a clinic of morality and knowledge. The need for creative and innovative management will ÃÂ evoke ÃÂ the ÃÂ brandÃÂ  imageÃÂ  ofÃÂ  MadrasahÃÂ  diniyah, ÃÂ which recently experienced a deterioration in terms of childrens education. ÃÂ In ÃÂ this ÃÂ era, ÃÂ the ÃÂ entry ÃÂ of ÃÂ westernÃÂ  culture ÃÂ into Indonesia is very influential on childrens education. This paper discusses the management of Madrasah Diniyah that is culture based. The type of approach used is qualitative descriptive that will provide direct benefits as a source of information to the public.